2016
DOI: 10.1103/physrevb.93.054411
|View full text |Cite
|
Sign up to set email alerts
|

Two-body problem of core-region coupled magnetic vortex stacks

Abstract: The dynamics of all four combinations of possible polarity and circularity states in a stack of two vortices is investigated by time-resolved scanning transmission x-ray microscopy. The vortex stacks are excited by unidirectional magnetic fields leading to a collective oscillation. Four different modes are observed that depend on the relative polarizations and circularities of the stacks. They are excited to a driven oscillation. We observe a repulsive and attractive interaction of the vortex cores depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Several multi-vortex systems have been explored for use in oscillators, including lateral vortex arrays [17] and vertically stacked vortex pairs. [18] Pairing of vortices can give rise to dynamic properties qualitatively different from those of the individual vortices constituting the pair, as has been shown in recent studies on lateral exchange-coupled vortex pairs [19] as well as vertical magnetostatically-coupled symmetric [20] and asymmetric [21,22] vortex pairs. The precise nature of the collective dynamics of a vortex pair depends on the strength of the inter-vortex interactions as well as the exact core/chirality configuration within the pair.…”
mentioning
confidence: 83%
“…Several multi-vortex systems have been explored for use in oscillators, including lateral vortex arrays [17] and vertically stacked vortex pairs. [18] Pairing of vortices can give rise to dynamic properties qualitatively different from those of the individual vortices constituting the pair, as has been shown in recent studies on lateral exchange-coupled vortex pairs [19] as well as vertical magnetostatically-coupled symmetric [20] and asymmetric [21,22] vortex pairs. The precise nature of the collective dynamics of a vortex pair depends on the strength of the inter-vortex interactions as well as the exact core/chirality configuration within the pair.…”
mentioning
confidence: 83%
“…On the other hand, the topological phase of magnetic materials is of great current interest in magnetism because of its fundamen-tal significance as well as in spintronics because of its practical utility for robust information processing [25][26][27][28][29][30][31][32]. A particularly interesting system is magnetic texture-based metamaterials since they can offer flexible controllability that can benefit from modern spintronic techniques [33][34][35][36][37][38][39][40][41]. Indeed, topological chiral edge states have been predicted in a twodimensional honeycomb lattice of magnetic textures (such as vortices and skyrmions) [42,43]; however, these states are first-order by nature, according to the classification of topological insulators.…”
Section: Introductionmentioning
confidence: 99%
“…17 A related memory idea based on resonantly depinning vortex-like domainwalls in a nanowire, the so-called race-track memory, was demonstrated to efficiently switch under spin-torque current excitation. 18 A number of recent studies focused on lateral exchange-coupled vortex pairs 19 and magnetostaticallycoupled vortex arrays [20][21][22][23][24] as well as on vertical vortex pairs [25][26][27] have shown that the inter-vortex coupling can significantly alter the vortex-pair dynamics, giving rise to new resonant modes of motion, not present in the isolated vortex case. We have previously shown that in the limit of strong core-core coupling in a vertical stack, with a monopole-like interaction of the two cores, the collec- Resistance versus in-plane field for a SAF magnetic junction in the parallel-core antiparallel-chirality (P-AP) vortex pair state.…”
Section: Introductionmentioning
confidence: 99%